Меthodological Potential of the Flipped Classroom Model in Science and Social Studies Classes - Sanja R. Blagdanić (University of Belgrade, Teacher Education Faculty, 2021)
In the last few years, the concept of a flipped classroom has become relevant and is increasingly being used as a teaching model. The first introduction to the teaching contents no longer takes place at school, but at the students’ home, through individual work. Teaching time is devoted to a more in-depth interpretation of the content. This paper presents the theoretical foundations of this model, the results of the previous research on the effectiveness of this model, as well as its implications in the Science and Social Studies classes. The aim of the conducted empirical research was to look at primary school teachers ‘awareness of the flipped classroom model, their attitudes about the possibilities of applying this way of working in teaching Science and Social Studies, as well as teachers’ self-assessment of their competencies for applying this model. The data were collected by an online survey of 105 teachers. The first part of the questionnaire examined teachers’ awareness of the flipped classroom model and the frequency of its use in teaching Science and Social Studies. The second part of the questionnaire provides an explanation of the flipped classroom model together with an example of a scenario for a Science and Social Studies class based on this model. Through six statements, the teachers assessed the methodological potential of this model of work, as well as their own ability for this form of work, taking into account the presented scenario and their teaching experience. The obtained results show that teachers are not fully informed about the flipped classroom model, which conditions its relatively rare application in teaching, regardless of the pedagogical experience of teachers. After offering an explanation of the flipped classroom model and an example of one Science and Social Studies lesson scenario based on it, most teachers expressed a positive attitude towards this model, pointing out its advantages in the conative-social aspect (positive impact on learning motivation, possibility of individualization, better communication between teachers and students), while they showed less confidence in the positive impact on student achievement. Teachers’ assessment of their own methodological competence for the application of this model shows that more than two thirds of teachers express the need for additional training for the application of the flipped classroom model in the first cycle of primary education.